Respuesta :

Hello from MrBillDoesMath!

Answer:

The topmost (blue shaded) rectangle.

Discussion:

Order the terms in each parentheses by decreasing exponent order:

( 6b^3 + 6 - b^4) - (8b^3-6b^4+ 2)   =

( - b^4 + 6b^3 + 6) - ( -6b^4 + 8b^3 + 2)     =>

Look at the second parentheses. Recall that the product of two negative values is positive so the above expression equals

( - b^4 + 6b^3 + 6) + ( 6b^4 - 8b^3 - 2)  

Combine like terms from both parentheses:

(-b^4+ 6b^4) + (6b^3-8b^3) + (6 - 2)     => simplify

5b^4              + ( -2b^3)         + 4            =>

5b^4 -2b^3 + 4

This is the topmost (blue shaded) rectangle.

Thank you,

MrB

akephd
(6b3+6-b4)-(8b3-6b4+2)=
6b3+6-b4-8b3+6b4-2=
5b4-2b3+4
So your answer is the first choice